Increased Handpiece Speeds without Air Coolant: Aerosols and Thermal Impact. (January 2023) - Vernon, J.J.; Lancaster, P.E.; Black, E.V.I.; Devine, D.A.; Fletcher, L.; Wood, D.J.; Nattress, B.R.
This study assessed the impact of increased speed of high-speed contra-angle handpieces (HSCAHs) on the aerosolization of a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) surrogate virus and any concomitant thermal impact on dental pulp. A bacteriophage phantom-head model was used for bioaerosol detection. Crown preparations were performed with an NSK Z95L Contra-Angle 1:5 (HSCAH-A) and a Bien Air Contra-Angle 1:5 Nova Micro Series (HSCAH-B) at speeds of 60, 000, 100, 000, and 200, 000 revolutions per minute (rpm), with no air coolant. Bioaerosol dispersal was measured with Φ6-bacteriophage settle plates, air sampling, and particle counters. Heating of the internal walls of the pulp chambers during crown preparation was assessed with an infrared camera with HSCAH-A and HSCAH-B at 200, 000 rpm (water flows ≈15 mL min −1 and ≈30 mL min −1 ) and an air-turbine control (≈23.5 mL min −1 ) and correlated with remaining tissue thickness measurements. Minimal bacteriophage was detected on settle or air samples with no notable differences observed between handpieces or speeds ( P > 0.05). At all speeds, maximum settled aerosol and average air detection was 1.00 plaque-forming units (pfu) and 0.08 pfu/m 3, respectively. Irrespective of water flow rate or handpiece, both maximum temperature (41.5°C) and temperature difference (5.5°C) thresholds for pulpal health were exceeded more frequently with reduced tissue thickness. Moderate and strong negative correlations were observed based on Pearson's correlation coefficient, between remaining dentine thickness and either differential ( r = −0.588) or maximum temperature ( r = −0.629) measurements, respectively. Overall, HSCAH-B generated more thermal energy and exceeded more temperature thresholds compared to HSCAH-A. HSCAHs without air coolant operating at speeds of 200, 000 rpm did not increase bioaerosolization in the dental surgery. Thermal risk is variable, dependent on handpiece design and remaining dentine thickness.